Clusters of incompatible genotypes evolve with limited dispersal - Landguth, Erin L.; Johnson, Norman A.; Cushman, Samuel A. (Frontiers in Genetics, 2015)
Theoretical and empirical studies have shown heterogeneous selection to be the primary driver for the evolution of reproductively isolated genotypes in the absence of geographic barriers. Here, we ask whether limited dispersal alone can lead to the evolution of reproductively isolated genotypes despite the absence of any geographic barriers or heterogeneous selection. We use a spatially-explicit, individual-based, landscape genetics program to explore the influences of dispersal strategies on reproductive isolation. We simulated genetic structure in a continuously distributed population and across various dispersal strategies (ranging from short- to long-range individual movement), as well as potential mate partners in entire population (ranging from 20 to 5,000 individuals). We show that short-range dispersal strategies lead to the evolution of clusters of reproductively isolated genotypes despite the absence of any geographic barriers or heterogeneous selection. Clusters of genotypes that are reproductively isolated from other clusters can persist when migration distances are restricted such that the number of mating partners is below about 350 individuals. We discuss how our findings may be applicable to particular speciation scenarios, as well as the need to investigate the influences of heterogeneous gene flow and spatial selection gradients on the emergence of reproductively isolating genotypes.